2022
DOI: 10.1016/j.amp.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Les accès psychotiques aigus liés à la pandémie COVID-19

Abstract: Le monde traverse actuellement une période extrêmement stressante à cause de la pandémie du COVID-19. Cette situation exceptionnelle et alarmante pourrait augmenter l’incidence des problèmes de santé mentale, parmi lesquels les troubles psychotiques aigus. Notre observation rapporte deux cas de patients présentant un accès psychotique aigu, avec une thématique délirante en relation avec la pandémie du coronavirus. Les deux patients, qui ne présentaient pas d’antécédents antérieurs de troubles psychiatriques, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Some patients presented features complicating diagnosis: On two occasions(Dhir et al, 2020;Ambar Akkaoui et al, 2021), self-treatment with different drugs might have contributed to psychosis. Cannabis consumption with low intensity was reported in one case(Marouda et al, 2021), with high intensity in two cases(Doufik et al, 2021;Marín et al, 2021). The authors of the latter paper attributed psychotic symptoms to cannabis withdrawal syndrome (due to lockdown and quarantine).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Some patients presented features complicating diagnosis: On two occasions(Dhir et al, 2020;Ambar Akkaoui et al, 2021), self-treatment with different drugs might have contributed to psychosis. Cannabis consumption with low intensity was reported in one case(Marouda et al, 2021), with high intensity in two cases(Doufik et al, 2021;Marín et al, 2021). The authors of the latter paper attributed psychotic symptoms to cannabis withdrawal syndrome (due to lockdown and quarantine).…”
mentioning
confidence: 98%
“…Belvederi Murri et al(2021) reported the case of a female student of Chinese origin living in Italy who became acutely psychotic during the first lockdown and in whom discreet psychotic symptoms had been present already 10 months before. The other patient was a male with a 1-month history of changed behaviour who responded quickly on treatment with AP(Doufik et al, 2021). Eight times (12.8%) the diagnosis 'psychosis' was given without further specification.…”
mentioning
confidence: 99%
“…Wang et al [ 26 ] reported a meta-analysis to show that 6.7% of pediatrics patients developed nervous system symptoms caused by COVID-19. Doufik et al [ 27 ] reported a case study of two patients who developed acute psychotic disorders with a delusional theme related to the COVID-19 pandemic. Tzur-Bitan et al [ 28 ] showed individuals with schizophrenia, a mental health disease, may have a higher risk for COVID-19 morbidity.…”
Section: Resultsmentioning
confidence: 99%